PATH-37. IDENTIFYING HIGH-RISK PATIENTS FOR WHO GRADE I MENINGIOMA RECURRENCE USING HISTOPATHOLOGICAL FEATURES AND THE MIB-1 INDEX. (9th November 2020) - Haddad, Alexander; Young, Jacob; Kanungo, Ishan; Sudhir, Sweta; Chen, Jia-Shu; Raleigh, David; Magill, Stephen; McDermott, Michael; Aghi, Manish
Abstract: BACKGROUND: In this study, we identify clinical, radiographic, and histopathologic prognosticators of overall, early, and post-median recurrence in World Health Organization (WHO) grade I meningiomas. We also determine a clinically relevant cutoff for MIB-1 to identify patients at high risk for recurrence. METHODS: A retrospective review of WHO grade I meningioma patients with available MIB-1 index data who underwent treatment at our institution from 2007-2017 was performed. Univariate and multivariate analyses, and recursive partitioning analysis (RPA), were used to identify risk factors for overall, early (within 24 months), and post-median (greater than 24 months post-treatment) recurrence. RESULTS: A total of 239 patients were included. The mean age was 60.0 years, and 69.5% of patients were female. The average follow-up was 41.1 months. All patients received surgery and 2 patients each received either adjuvant radiotherapy or gamma knife treatment. The incidence of recurrence was 10.9%, with an average time to recurrence of 33.2 months (6-105 months). Posterior fossa tumor location (p=0.004), MIB-1 staining (p=0.008), nuclear atypia (p=0.003), and STR (p< 0.001) were independently associated with an increased risk of recurrence on cox-regression analysis. RPA for overall recurrence highlighted extent of resection, and after gross total resection (GTR), a MIB-1 index cutoff of 4.5% as key prognostic factors for recurrence. Patients with a GTR and MIB-1 >4.5% had a similar incidence of recurrence as those with STR (18.8vs.18.6%). Variables independently associated with early recurrence on binary logistic regression modeling included STR (p=0.002) and nuclear atypia (p=0.019). RPA confirmed STR as associated with early recurrence. MIB-1 index (p=0.010) was identified as an independent predictor of post-median recurrence using similar methods. CONCLUSIONS: STR, posterior fossa location, nuclear atypia, and elevated MIB-1 index are prognostic factors for WHO grade I meningioma recurrence. Moreover, MIB-1 index >4.5% is prognostic for recurrence in patients with GTR.